2000
DOI: 10.1182/blood.v95.8.2630
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor and interleukin-6 in paracrine tumor-stromal cell interactions in multiple myeloma

Abstract: Vascular endothelial growth factor (VEGF), a multifunctional cytokine, potently stimulates angiogenesis including tumor neovascularization. Although well established in solid tumors, the role of VEGF in bone marrow neoangiogenesis and paracrine tumor-stromal cell interactions in lymphohematopoietic malignancies has not been fully elucidated. In multiple myeloma (MM), marrow neovascularization parallels disease progression. This parallel prompted us to investigate the expression and secretion of VEGF by myeloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
1
19

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 485 publications
(144 citation statements)
references
References 49 publications
4
120
1
19
Order By: Relevance
“…Oxygen deficiency is a strong stimulus, but not the only stimulus for enhanced VEGF synthesis. It has been suggested that IL-6 (Takada et al 1997) and IL-1β (Haq et al 1998) are involved in post-ischaemic renal failure and it has also been shown that they increase VEGF synthesis in vitro (Gloddek et al 1999;Dankbar et al 2000;Levitas et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen deficiency is a strong stimulus, but not the only stimulus for enhanced VEGF synthesis. It has been suggested that IL-6 (Takada et al 1997) and IL-1β (Haq et al 1998) are involved in post-ischaemic renal failure and it has also been shown that they increase VEGF synthesis in vitro (Gloddek et al 1999;Dankbar et al 2000;Levitas et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed on a variety of cultured cells demonstrated that VEGF mRNA and protein expression are markedly increased by hypoxia (Shweiki et al 1992;Ladoux & Frelin, 1993) and different cytokines (Gloddek et al 1999;Finkenzeller et al 1992;Stavri et al 1995;Dankbar et al 2000;Levitas et al 2000). In vivo studies have also shown that VEGF mRNA and protein expression are increased in response to ischaemic injury of different organs (Banai et al 1994;Bernaudin et al 2002).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…MM derived ECs are endowed of an over-angiogenic phenotype able to support directly the growth, proliferation, and invasion of MM through the direct secretion of several growth factors, including IL-6 (146). For example, a cross-talk between MM cells and ECs has been described, where MM cells secrete VEGF that stimulates ECs to produce IL-6; this crosstalk ultimately determines simultaneous proliferation of both MM cells and ECs (147). MM ECs, but not MGUS ECs, are able to spontaneously secrete several other growth factors, including bFGF and HGF, which also promote MM cell proliferation and survival (148).…”
Section: Endothelial Cells and Bm Vessel Formation In MMmentioning
confidence: 99%
“…Transcriptional factors specific for myeloma cells, such as IRF4, Blimp-1 (PRDM1), and XBP1, are also transcribed in BMMCs [26][27][28][29]. Upregulation of nourishing growth factors for myeloma, such as HGF, IGF1, and VEGF [30][31][32][33], was also confirmed. Furthermore, tumorigenic genes correlated with PC1 [34][35][36][37][38][39] (Fig.…”
Section: Single-cell Rna-seq Identifies Myeloma Cells From Normal Cellsmentioning
confidence: 96%